Genetic variability, correlation and path analysis of yield and yield contributing characters in wheat (Triticum aestivum L.) under normal and terminal heat stress condition - Das, Anannya; Das, Arpan; Muntaha, Sidratul; Akhter, Shirin; Sagor , G. H. M. Sagor (Fundamental and Applied Agriculture, 2024)
Genetic variability and characters association studies play a pivotal role in enhancing selection efficiency under stress condition in plants. Therefore, the study was aimed at assessing the impact of terminal heat stress on various morpho-physiological traits and their association in wheat under control and terminal heat stress condition. The experiment was conducted using thirty-five wheat genotypes in a Randomized Complete Block design (RCBD) plots on three different sowing dates to induce terminal heat stress. A range of 11 morpho-physiological parameters were assessed. All of the traits showed significant variations under studied conditions. Estimates of the genotypic and phenotypic coefficients of variation (GCV and PCV) showed that PCV was higher than GCV indicating large environmental influence on the expression of the traits under study. High GCV and PCV were observed in grain per plant and yield per plant in both normal and heat stress conditions. Chlorophyll content, grain per plant and yield per plant showed highest heritability with high genetic advance (GA) under both normal and terminal heat stress condition. According to the results of the path co-efficient analysis, grain per plant had a strong positive connection with grain yield and plant height and days to 50% flowering had a negative correlation with grain yield per plant under both normal and stress condition. Canopy temperature has direct negative effect on yield in stress condition. The identified traits can be used as effective selection criteria under terminal heat stress condition to develop high yielding heat tolerant wheat variety.